T-element analysis of plates on unilateral elastic Winkler-type foundation - Jirousek, Jaroslav; Zieliński, Andrzej P.; Wróblewski, Adam (Computer Assisted Methods in Engineering and Science, 2023)
This paper presents a hybrid-Trefftz finite element algorithm designated as fictitious load approach. Its originality resides in the formulation and practical application of concepts which make it possible to account for the unilateral contact conditions of a plate without modification of the finite element mesh. To reach this aim, the approach allows the movable interface between the contact and non-contact parts of the plate to travers any finite element subdomain. The adjustments are confined to fictitious load dependent terms, while the element stiffness matrices remain unchanged during the whole iterative process. Several numerical examples are analysed to assess the effectivity of the T-element algorithm and to compare it with some of the existing solutions of the same problem.